Microservices Design and Development for the Basic Logistic Functionalities in the Unified Process - Benny Susanto; Fitrah Rumaisa (SAFE-Network, 2023)
The software development process has gone through significant change in the recent years. Now delivering a system that merely satisfies functional requirements is no longer enough. Companies want their systems to be easily maintained, scalable, fault tolerant, available, integrated, and other attributes. The microservice architecture was designed to create such a robust system where a big monolith system is broken down into multiple small services that communicate each other to fulfill the requirements. One area of functional requirements that exist and needed in almost all kind of companies is the logistic part. This paper will discuss how microservices architecture can be designed and implemented to support logistic functionality that can be reused in a lot of companies as the base system.